2015
DOI: 10.1021/acs.langmuir.5b01458
|View full text |Cite
|
Sign up to set email alerts
|

Toward Accumulation of Magnetic Nanoparticles into Tissues of Small Porosity

Abstract: Magnetic concentration of drug-laden magnetic nanoparticles has been proven to increase the delivery efficiency of treatment by 2-fold. In these techniques, particles are concentrated by the presence of a magnetic source that delivers a very high magnetic field and a strong magnetic field gradient. We have found that such magnetic conditions cause even 150 nm particles to aggregate significantly into assemblies that exceed several micrometers in length within minutes. Such assembly sizes exceed the effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Previous research suggests that hydrodynamic interactions and dipole relaxation both affect the frequency dependence of magnetic doublet rotation in rotating fields. It has been observed that doublets rotate at the same frequency as rotating fields up to a critical frequency, after which the rotation rate declines due to viscous drag [8,23,28,29]. These studies showed at frequencies slightly higher than the critical frequency: (1) individual dipoles no longer remain aligned along the line of centers, (2) for freely rotating doublets, the interparticle distance oscillates, and (3) for both rigid and freely rotating doublets, the angular trajectories oscillate about an average steady rotational velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that hydrodynamic interactions and dipole relaxation both affect the frequency dependence of magnetic doublet rotation in rotating fields. It has been observed that doublets rotate at the same frequency as rotating fields up to a critical frequency, after which the rotation rate declines due to viscous drag [8,23,28,29]. These studies showed at frequencies slightly higher than the critical frequency: (1) individual dipoles no longer remain aligned along the line of centers, (2) for freely rotating doublets, the interparticle distance oscillates, and (3) for both rigid and freely rotating doublets, the angular trajectories oscillate about an average steady rotational velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Under a dynamic magnetic field, the switchable magnetic field direction can cause the particles to group into an attractive or repulsive configuration, promoting the particle clusters to assemble or disassemble. Thus, this reverse property was utilized to create a simple analytical model to evaluate the kinetic thresholds of the assembly and disassembly of magnetic nanoparticles, and these methods demonstrated good tumor penetration into a gel with a similar pore size as that of tumor tissue [18].…”
Section: Tumor Penetration By Size Changeabilitymentioning
confidence: 99%
“…Therefore, previously in a simulation, we solved the sticking issue by intentionally changing the magnetic field direction, and the use of dynamic magnetic actuation (change in field direction) for reducing aggregation [ 21 ]. The experimental results in [ 22 ] showed that the dynamic actuation with a pulse-shaped magnetic field using permanent magnets can improve crossing of the cell barrier.…”
Section: Introductionmentioning
confidence: 99%